Customer Satisfaction in Automobile Industry in Kathmandu District (Sahayaatra सहयात्रा, 2023)
This study aims to evaluate the relationship between the satisfaction of customers in terms of after-sales services in the automobile industry in Kathmandu. This study applied a descriptive research design. This study type was quantitative. Since the population is unknown in this study 384 questionnaires were collected from respondents of this research work applying a purposive sampling technique. The population of the study was both two-wheelers and four-wheeler vehicle users from many places in Kathmandu and various backgrounds. Purposive sampling techniques were used in this study. This study applied the self-administered close-ended survey questionnaire. Multiple choice questions based on the Five-Point Likert Scale developed by Rensis Likert were used to mention a level of a statement of disagreement to an agreement where 1 indicates strongly disagree and 5 indicates strongly agree. Data were analyzed based on the majority of respondents/ responses collected out of the total sample size (384) entered in the table of the Five-Point Likert Scale. Respondents who are in favor of an agreement with all of the tables and statements are more than those of disagree. Therefore, it can be concluded that there is a high association between the satisfaction of customers with components of after-sales service i.e., the cost of service, service quality, responsiveness, and speed of service of automobiles in various places in Kathmandu. It can be concluded that these components are associated with customer satisfaction. The automobile industry should be guided by the Kano model to meet the requirements of consumers in terms of products and services.